Understanding financial inclusion in Ethiopia - Workineh Ayenew (Cogent Economics & Finance, 2022)
The main objective of this paper is to examine the drivers, barriers of financial inclusion, and saving and credit behaviour in Ethiopia. We used the World Bank 2017 Findex database to carry out logit estimations. We found that being educated, richer, a man, and older associated with greater level of financial inclusion with a strong influence of income and education. We found that the existing gender gaps in the financial inclusion is mainly due to women exclusion from the non-financial sector. While younger and poor adults do not access formal accounts due to involuntary exclusion (distance to the nearest financial access point, affordability, and lack of documentation), older and richer individuals are constrained by voluntary barriers (lack of money, family member has account). Women are less likely to save for farm or business and old age security purposes, while educated individuals in the wealthiest 20% quintile save for old age security purposes. The rich and the poor seek formal credit primarily for farm/business and asset purchase. Our work confirms that the determinants, barriers, saving, and credit behaviour are different across individual characteristics. We strongly recommend that policies that aim to foster financial inclusion should target the vulnerable (the poor, young, less educated, and women) population groups. Authorities and policymakers should strive to improve women participation in the formal real sector of the economy, financial institutions should adopt technologies such as mobile banking and mobile money to ensure the accessibility of financial services.
Keywords: 330; Ethiopia; financial inclusion; global findex; logit model; Economics; Macroeconomics; Finance